Pharmacist-led HIV and hepatitis C point-of-care testing and risk mitigation counseling in individuals experiencing homelessness - Sorosh Kherghehpoush; Kimberly C. McKeirnan (Elsevier, 2021)
Introduction: Over half a million people experience homelessness on any given night in the United States. As a result of increased exposure to disease, violence, stigma, substance misuse and limited accessibility to health services, individuals experiencing homelessness are disproportionately affected by communicable diseases such as HIV and HCV with prevalence estimates as high as 21% and 36%, respectively. Pharmacists, being some of the most trusted and accessible healthcare providers, are in a unique position to have a significant impact on the nationwide initiatives in Ending the HIV Epidemic: A Plan for America and the National Viral Hepatitis Plan by offering preventative testing services and patient-centered risk mitigation counseling and education. This research looks to assess the health impacts associated with pharmacist-led HIV and HCV screening coupled with comprehensive education and risk mitigation counseling in adults experiencing homelessness. Methods: This study was conducted in a single independent community pharmacy in Spokane, Washington which specializes in mental health services and serves a large proportion of patients who are experiencing homelessness. Study participants are walk-in patients of the pharmacy, over the age of 18, are currently experiencing homelessness, and have not received an HIV or HCV screening within the past 6 months. The study intervention includes a Risk Determination interview, administration of HIV and HCV point-of-care antibody test, comprehensive diseases state education and personalized risk mitigation counseling. Participants are then referred to a local health clinic for confirmatory testing, anonymous partner notification, and evaluation for pre-exposure prophylaxis if indicated. Results: A total of 10 participants were included in the final data analysis. Majority of study participants were male (80%), heterosexual (90%) and over the age 30 (90%). A total of 8 participants (80%) had a reactive HCV screening and there were no reactive HIV screenings. Many of participants reported IV drug use with methamphetamine being the most used illicit substance. Half of all participants (50%) admitted to borrowing a needle for injection drug use within the past 6 months. Two participants admitted to having sexual intercourse with a partner who was known to be HCV-positive and both participants had a reactive HCV screening. All study participants reported at least one serious mental illness diagnosis and ongoing recreational drug use was cited as a coping mechanism in all participants. Conclusion: Since efficacy of treatment is no longer the limiting factor in eradicating HCV and suppressing HIV viral load, public health efforts need to be refocused on patient engagement through preventative services in an environment that is less stigmatized than traditional testing sites, such as community pharmacies. Study participants were highly receptive to pharmacist-provided point-of-care screening services in the community pharmacy. Combining HIV and HCV point-of-care testing with comprehensive patient-centered education and risk mitigation counseling may result in lower rates of community transmission, improve linkage to care and may lead to long-term retention of marginalized populations such as those experiencing homelessness.